Magnetic and electrical properties connections for the Argentines archipelago islands rocks - Shepel, S. I.; Savenko, B. Ya.; Kravchuck, M. V. (Ukrainian Antarctic Journal, 2006)
The investigation of connections of physical parameters of rocks is important geophysical problem. The existence of relations between electrical and magnetic parameters of crystalline rocks of the Argentines archipelago was determined. Correlation dependences are more distinct for relation between magnetic susceptibility and dielectric constant. Direct proportionality between magnetic susceptibility and remanent magnetization was fixed. The density influence on changes of some electrical and magnetic parameters were determined. Electrical and magnetic parameters variations and their relation are depended on petrochemistry and genetic features of ore minerals.